Evaluation of an elective ultrasound course for medical students. Issue 3 (8th February 2022) - Kloth, Christopher; Schmidt, Stefan Andreas; Graeter, Tilmann; Nikolaou, Konstantin; Kaufmann, Sascha; Beer, Meinrad; Thaiss, Wolfgang Maximilian
Abstract: To evaluate the educational benefits of teaching ultrasound in an elective radiological course for medical students. We conducted a single‐center retrospective analysis of a one‐week elective ultrasound course in which 39 medical students (25 female; median age 25.8 ± 2.8 years, range 21–35, 4th and 5th years of undergraduate medical education) participated as part of their radiological training. The students completed a pre‐ and post‐course questionnaire using a five‐point Likert scale for self‐assessment of technical knowledge, confidence in the procedure regarding different organs, motivation for performing ultrasound, and the importance of ultrasound in medical education. The students also assessed the value of ultrasound teaching in the context of their general medical degree. Pre‐test and post‐test scores showed significantly improved radiology knowledge ( p  ≤ 0.001) concerning all abdominal organs (liver, spleen, gallbladder, kidney, urinary bladder, aorta and retroperitoneum). A significant improvement was registered in performing ultrasound of peripheral arteries and venous structures (each p  = 0.001), and also of the thyroid gland ( p  = 0.006). General surveys at the end of the elective were overwhelmingly positive, with constructive criticism and complimentary comments. Systematic training in ultrasound markedly improved the students' skills. This was especially pronounced for solid organ structures, while students requested more education regarding the retroperitoneum and vascular structures. Teaching ultrasound in an elective hands‐on training course improves anatomical understanding and practical skills associated with increased motivation. The results affirm the necessity and clinical relevance of the course during the radiological training of medical students.